Cancer risk in different generations of Middle Eastern immigrants to California, 1988–2013 - Ziadeh, Clara (Int J Cancer, 2017)
The objective of this study is to compare cancer risk among different generations of Middle Eastern immigrants (ME) and non-Hispanic whites (NHW) in California between 1988 and 2013. We used data from the California Cancer Registry to identify invasive primary incident cancer cases in three population groups: (i) first-generation ME immigrants, (ii) second- or subsequent-generations ME immigrants, and (iii) NHW. Proportional incidence ratio (PIR) was used to compare cancer risk of the 15 selected most common cancers in the 3 population groups taking into consideration time since immigration for first-generation ME immigrants. First generation ME immigrants were more likely to be at increased risk of stomach (PIR= 3.13) and hepatobiliary (PIR=2.27) cancers in females and thyroid (PIR=2.19) and stomach (PIR=2.13) cancers in males in comparison with NHW. Second- or subsequent-generations ME immigrants were at increased risk of thyroid cancer (PIR=1.43 in females and 2.00 in males) in comparison with NHW, and malignant melanoma cancer (PIR=4.53 in females and 4.61 in males) in comparison with first-generation ME immigrants. The risk levels of breast, thyroid and bladder cancers in ME first generation were significantly higher compared to NHW regardless of time spent in the United States suggesting the role of genetic predisposition, and/or cultural characteristics associated with these cancers. The results suggest that differences in cancer risk between ME first-generation immigrants and NHW change in second or subsequent generations, approaching the risk level of NHW and indicating the impact of acculturation in this immigrant population.